Balancing intubation time with postoperative risk in cardiac surgery patients – a retrospective cohort analysis - Kotfis K; Szylińska A; Listewnik M; Lechowicz K; Kosiorowska M; Drożdżal S; Brykczyński M; Rotter I; Żukowski M (Dove Medical Press, 2018)
Katarzyna Kotfis,1 Aleksandra Szylińska,2 Mariusz Listewnik,3 Kacper Lechowicz,1 Monika Kosiorowska,3 Sylwester Drożdżal,1 Mirosław Brykczyński,3 Iwona Rotter,2 Maciej Żukowski1 1Department of Anesthesiology, Intensive Therapy and Acute Intoxications, Pomeranian Medical University, Szczecin, Poland; 2Department of Medical Rehabilitation and Clinical Physiotherapy, Pomeranian Medical University, Szczecin, Poland; 3Department of Cardiac Surgery, Pomeranian Medical University, Szczecin, Poland Introduction: Intubation time in patients undergoing cardiac surgery may be associated with increased mortality and morbidity. Premature extubation can have serious adverse physiological consequences. The aim of this study was to determine the influence of intubation time on morbidity and mortality in patients undergoing cardiac surgery.Methods: We performed a retrospective analysis of data on 1,904 patients undergoing isolated coronary artery bypass grafting (CABG) and stratified them by duration of intubation time after surgery – 0–6, 6–9, 9–12, 12–24 and over 24 hours. Postoperative complications risk analysis was performed using multivariate logistic regression analysis for patients extubated ≤12 and >12 hours.Results: Intubation percentages in each time cohort were as follows: 0–6 hours – 7.8%, 6–9 hours – 17.3%, 9–12 hours – 26.8%, 12–24 hours – 44.4% and >24 hours – 3.7%. Patients extubated ≤12 hours after CABG were younger, mostly males, more often smokers, with lower preoperative risk. They had lower 30-day mortality (2.02% vs 4.59%, P=0.002), shorter hospital stay (7.68±4.49 vs 9.65±12.63 days, P<0.001) and shorter intensive care unit stay (2.39 vs 3.30 days, P<0.001). Multivariate analysis showed that intubation exceeding 12 hours after CABG increases the risk of postoperative delirium (OR 1.548, 95% CI 1.161–2.064, P=0.003) and risk of postoperative hemofiltration (OR 1.302, 95% CI 1.023–1.657, P=0.032).Conclusion: Results indicate that risk of postoperative complications does not increase until intubation time exceeds 12 hours. Shorter intubation time is seen in younger, men and smokers. Intubation time >12 hours is a risk factor for postoperative delirium and hemofiltration after cardiac surgery. Keywords: intubation, cardiac surgery, CABG, mortality, complications, delirium